Implementasi MQTT (Message Queuing Telemetry Transport) pada Sistem Monitoring Jaringan berbasis SNMP (Simple Network Management Protocol) - Akbar Pandu Segara; Rakhmadhany Primananda; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The growing use of current information technology users, monitoring system is needed to facilitate network administrators to monitor the devices connected in a computer network. Currently network monitoring systems generally display information by polling device data every few minutes. This causes the administrator don't know as early as possible if something happens to the device being monitored. This study developed an SNMP based network monitoring system by implementing MQTT. MQTT uses the principle of publish-subscribe to communicating. MQTT is used because power-saving and lightweight messaging protocol. This research produces a network monitoring system which can monitored device information like CPU, load, and memory periodically and display it in graphical form and table in web interface. System development with implementing SNMP agent on monitored device and SNMP manager on NMS Server as publisher. Manager requested information to agent every 2 seconds. On the client side is implemented a subscriber to subscribe published data by manager and then processed on the web-based interface. From the test results show the processing time data by the server and client takes an average time of 2.029 seconds. For data processing time from server to client takes an average time of 1.210 seconds.